The Role of Internal Audit on Financial Performance Under IIA Standards: A Survey Study of Selected Iraqi Banks - Naji Afrasyaw Fatah; Hawkar Anwer Hamad; Khwanas Saeed Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aimed to demonstrate the importance of internal auditing standards issued by the American Institute of Internal Auditors (IIA) in the financial performance of commercial banks in Iraq. Moreover, the researchers sought to determine the impact of internal audit on financial performance under the standards of the Institute of Internal Auditors (IIA) in the surveyed banks. Furthermore, the study selected managers and auditors in the selected banks. The researchers designed a survey questionnaire and handed over to the target professionals for the data collection as it is the suitable tool and solution to collect data. While for the data analysis, Descriptive analysis and inferential statistical methods were used. The study fetched the conclusion that the financial performance of commercial banks has a positive affiliation with internal auditing standards. The respondents indicate that Iraqi commercial banks are still not highly subject to international standards for internal auditing and that all members of the research sample did not agree highly on the statements related to the application of internal auditing standards in their activities. The result of the regression model found that an increase in one unit in internal auditing standards could provide a growth in financial performance. Hence, this study suggests that the Iraqi commercial banks must implement an effective internal audit processes like internal auditing standards in order to improve the financial performances of the banks.